71.5k views
2 votes
Rewrite the equation by completing the square.
4x^2 + 28x + 49=0

User Roubi
by
5.7k points

2 Answers

6 votes

Answer:

g(x)=4(x-7/2)^2+0

Explanation:

Got it on Khan academy DO NOT USE THE ANSWER ABOVE INCORRECT

User Raspacorp
by
6.4k points
6 votes

Answer:


4(x+3.5)^(2)=0

Explanation:

we have


4x^(2)+28x+49=0

step 1

Group terms that contain the same variable, and move the constant to the opposite side of the equation


(4x^(2)+28x)=-49

step 2

Factor the leading coefficient


4(x^(2)+7x)=-49

step 3

Complete the square. Remember to balance the equation by adding the same constants to each side


4(x^(2)+7x+3.5^2)=-49+(3.5^2)(4)


4(x^(2)+7x+12.25)=0

step 4

Rewrite as perfect squares


4(x+3.5)^(2)=0

User IntegrateThis
by
6.2k points